2016
DOI: 10.1111/coa.12592
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical increase in nasal airway resistance after topical nasal decongestion – does it really exist? A retro‐ and prospective study

Abstract: The results indicate the existence and reproducibility of paradoxically increased nasal airway resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
7
0
4
Order By: Relevance
“…In the present study, the nasal airflow area measured with the Glatzel mirror decreased in only one child (patient 6) after applying the nasal cleansing and massage technique. A retrospective study on 36 patients with paradoxically increased airway resistance analyzed in their previous rhinomanometry data a group of patients with vasodilation after taking vasoconstrictors 18 . No studies were found proving the reasons behind this mechanism; however, it may be related to chronic rhinitis 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the nasal airflow area measured with the Glatzel mirror decreased in only one child (patient 6) after applying the nasal cleansing and massage technique. A retrospective study on 36 patients with paradoxically increased airway resistance analyzed in their previous rhinomanometry data a group of patients with vasodilation after taking vasoconstrictors 18 . No studies were found proving the reasons behind this mechanism; however, it may be related to chronic rhinitis 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Observou-se, no entanto, no presente estudo que uma única criança (PCT 6) apresentou diminuição na área da aeração nasal do espelho de Altmann, após a aplicação da técnica de limpeza e massagem nasal. Em um estudo retrospectivo, formado por 36 pacientes com resistência das vias aéreas paradoxalmente aumentadas, analisou-se nos dados da rinomanometria anterior um grupo de pacientes que apresentaram vasodilatação após o uso de vasoconstritor 18 . Não foram encontrados estudos que comprovem o porquê deste mecanismo, no entanto pode estar relacionado à presença de rinite crônica 19 .…”
Section: Discussionunclassified
“…DR, which is a key biomechanical parameter of the elastic strain model (2), may be calculated using 3D-CT reconstruction techniques. Therefore, using 3D-CT reconstruction techniques to measure the DR of the nasal septum at maximum deviation sites, the present study aimed to determine whether DR is associated with visual analogue scale (VAS) and nasal airway resistance (NAR) (2,6), and to evaluate the application of DR measurements in nasal septoplasty endoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%